Analisis Yuridis Tindak Pidana Penistaan Agama melalui Media Sosial TikTok dan YouTube (Studi Putusan Nomor 2771/Pid.Sus/2022/PN.Mdn) - Vallensia, Devita; Gunawan, Frederich; Emmanuel Sutanto, Theodore Francisco; Tirta, Marcell; Zebua, Johan Kristian (Fakultas Syariah IAI Muhammadiyah Bima, 2026)
This study aims to analyze the application of criminal law to acts of blasphemy committed through social media, particularly in Decision Number 2771/Pid.Sus/2022/PN.Mdn. This research is a normative juridical study employing statutory, case, and conceptual approaches, utilizing primary, secondary, and tertiary legal materials analyzed qualitatively. The results indicate that the application of Article 28 paragraph (2) in conjunction with Article 45A paragraph (2) of the Electronic Information and Transactions Law has fulfilled the elements of the criminal offense, including intent and the potential to incite hatred based on SARA (ethnicity, religion, race, and inter-group relations). The judges’ considerations were based not only on juridical aspects but also on the social impact of the act and the defendant’s attitude during the trial. From the perspective of sentencing theory, the decision reflects a combined approach between retributive and preventive objectives. However, the effectiveness of criminal sanctions in creating a deterrent effect remains a challenge. The study also highlights the tension between freedom of expression and the protection of religious values in the digital era, emphasizing the need for preventive measures such as improving digital literacy and promoting religious tolerance within society.